ANALISA STRATEGI PENGARUH INFLUENCER MARKETING DI SOCIAL MEDIA, ONLINE ADVERTISING DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN: (Studi Kasus Pada Toko On Line Zalora) - Prasetya, Adhitya Yoga; Astono, Ari Dwi; Ristianawati, Yuyun (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
The use of virtual and net technologies has led to revolutionary changes in the way companies meet consumer demands. Digital marketing is the use of the internet and technology to expand marketing networks. Digital marketing aims to get consumers and potential customers quickly. The acceptance of virtual and net technology in consumers is so wide that virtual marketing is the main choice for companies. The purpose of this study was to determine: 1) the influence of influencer marketing on social media on purchasing decisions at Zalora On Line Stores in Central Java; 2) the influence of online advertising on purchasing decisions at Zalora On Line Stores in Central Java; and 3) the effect of content marketing on purchasing decisions at Zalora On Line Stores in Central Java. The population of this study are consumers who have bought goods at Zalora On Line Stores in Central Java. Sampling by purposive sampling method, obtained a sample of 202, the collection of statistics is done by using a questionnaire. The statistical analysis technique was carried out using simple linear regression analysis with SPSS software. The results showed that the influencer marketing variable on social media had a positive and significant effect on purchasing decisions of 4,053 with a significance level of 0.000; the online advertising variable has a significant positive effect on purchasing decisions of 4.884 with a significance level of 0.000; and the content marketing variable has a positive and significant effect on purchasing decisions of 4,598 with a significance level of 0.000. Overall, the independent variable has an effect of 41% on the dependent variable, and the remaining 59% is influenced by other variables not found in this study.